Peran Ilmu Dan Akhlakul Karimah Dalam Mengatasi Konflik Umat Islam Akibat Kebencian Dan Kejahilan Di Era Digital - Rizky Mahruzar Utama Rizky (Pascasarjana IAIN Metro, 2026)
This study analyzes the roles of knowledge and noble character (akhlakul karimah) in addressing conflicts among Muslims in the digital era, employing a social tafsir (exegesis) approach to the Qur’an. The research is motivated by the rising phenomena of hate speech, accusations of apostasy (takfir), religious disinformation, and social media polarization, all of which threaten to undermine Islamic brotherhood (ukhuwah Islamiyah). The study aims to examine the relevance of Qur’anic values ​​in confronting contemporary socio-religious conflicts stemming from digital hatred and ignorance. It utilizes a qualitative methodology involving library research and a thematic tafsir (maudhu’i) approach. Data sources include Qur’anic verses, hadith, exegetical texts, and contemporary scholarly articles concerning digital conflict, knowledge, noble character, and religious moderation. The findings indicate that digital hatred and ignorance are primary drivers of conflict among Muslims, resulting from low religious literacy, a weak culture of verification (tabayyun), and a lack of communication ethics on social media. The study reveals that knowledge serves as the foundation for cultivating moderate, critical, and tolerant attitudes, while noble character acts as a social instrument for preserving Islamic brotherhood through communication ethics, tolerance, and peaceful conflict resolution. Ultimately, the research affirms the strong relevance of social Qur’anic exegesis in addressing contemporary digital conflicts by strengthening digital literacy and religious moderation, and by internalizing Qur’anic moral values.